Kebijakan Pembangunan Infrastruktur Liquified Natural Gas Untuk Pemenuhan Kebutuhan Energi Listrik - Mailinda Eka Yuniza; Melodia Puji Inggarwati (Fakultas Hukum Universitas Islam Indonesia, 2022)
This study aims to determine the policy of fulfilling electrical energy in Indonesia and the policy of developing liquified natural gas (LNG) infrastructure in the fulfillment of electrical energy in Indonesia. The method used in this research is normative research so that the data used is secondary data collected through literature study. The results of the study conclude that first, the laws and regulations related to electricity in Indonesia are described in several electricity policies including the General Plan for the Provision of Electricity (RUPTL). The electricity policy currently being worked on by the government is the 35 GW Electricity Development Program based on the 2019-2028 RUPTL. Second, electricity infrastructure development policies are spread across various laws and regulations and decisions. The LNG infrastructure development policy itself is contained in the Decree of the Minister of Energy and Mineral Resources Number 13K/13/MEM/2020 on the Assignment of the Implementation of the Supply and Development of LNG Infrastructure and the Conversion of the Use of Oil Fuel with LNG in the Provision of Electric Power. This policy encourages the development of LNG infrastructure and has an impact on accelerating development towards meeting the needs of electrical energy, especially for eastern Indonesia. The challenge is that there are still LNG export commitments with other countries that have the potential to hinder the fulfillment of domestic LNG needs. Key Words: LNG infrastructure development policy; LNG AbstrakKajian ini bertujuan untuk mengetahui kebijakan pemenuhan energi listrik di Indonesia serta kebijakan pembangunan infrastruktur liquified natural gas (LNG) dalam pemenuhan energi listrik di Indonesia. Metode yang digunakan dalam penelitian ini adalah penelitian normatif sehingga data yang digunakan adalah data sekunder yang dikumpulkan melalui studi pustaka. Hasil penelitian menyimpulkan, bahwa pertama, peraturan perundang-undangan terkait ketenagalistrikan di Indonesia dijabarkan dalam beberapa kebijakan ketenagalistrikan diantaranya Rencana Umum Penyediaan Tenaga Listrik (RUPTL). Kebijakan ketenagalistrikan yang sedang dikerjakan oleh pemerintah saat ini adalah Program Pembangunan Ketenagalistrikan 35 GW berdasarkan RUPTL 2019-2028. Kedua, kebijakan pembangunan infrastruktur kelistrikan tersebar di berbagai peraturan perundang-undangan maupun keputusan. Kebijakan pembangunan infrastruktur LNG sendiri terdapat dalam Keputusan Menteri ESDM Nomor: 13K/13/MEM/2020 tentang Penugasan Pelaksanaan Penyediaan Pasokan dan Pembangunan Infrastruktur LNG serta Konversi Penggunaan Bahan Bakar Minyak dengan LNG dalam Penyediaan Tenaga Listrik. Kebijakan tersebut mendorong pembangunan infrastruktur LNG dan memberikan dampak bagi percepatan pembangunan menuju pemenuhan kebutuhan energi listrik khususnya bagi wilayah Indonesia timur. Tantangannya adalah masih terdapat komitmen ekspor LNG dengan negara lain yang berpotensi menghambat pemenuhan kebutuhan LNG dalam negeri. Kata-kata Kunci: Kebijkan pembangunan infrastruktur LNG; LNG